Antibacterial Activity Test of N-Hexan, Ethyl Acetate and Water from Ethanol Extract of Kitolod Leaf (Isotoma Longiflora (L.) C. Presl.) AGAINST Staphylococcus Aureus ATCC 25923 - Tatiana Siska Wardani; Triya Choirin Nisa; Kusumaningtyas Siwi Artini (Global Health Science Group, 2022)
Kitolod plant (isotoma longiflora (L) C.Presl) contains alkaloids, flavonoids, and saponins. The content of this compound has antibacterial activity. This study aims to determine the antibacterial activity of the n-hexane, ethyl acetate and water fractions from the ethanolic extract of kitolod leaves against Staphylococcus aureus, and to determine the most active fraction in inhibiting bacteria. This research is an experimental descriptive study. The ethanolic extract of kitolod leaves was obtained by maceration method using 96% ethanol solvent, the viscous extract obtained was fractionated with three solvents, and dissolved in 1% DMSO then tested for its antibacterial power by diffusion and dilution method against Staphylococcus aureus at concentrations of 15%, 20%, 25%, and 30% using ofloxacin positive control. The test results obtained were analyzed using the One Way Anova test followed by the Post Hoc Test using the Tukey method using SPSS16. The results of the test using the diffusion method showed that the ethanol extract, n-hexane fraction, ethyl acetate fraction and water fraction had antibacterial activity against Staphylococcus aureus. The most active fraction was the water fraction at a concentration of 30%, with an average inhibition zone diameter of 19.0 mm. The inhibitory power was lower than the positive control ofloxacin (28.3 mm). The dilution method of the water fraction showed a minimum inhibitory concentration and a minimum kill concentration at a concentration of 15%.